From victorious rebels to strong authoritarian parties: prospects for post-war democratization. Issue 6 (18th September 2016) - Lyons, Terrence
ABSTRACT: In a number of cases, rebel movements that won civil wars transformed into powerful authoritarian political parties that dominated post-war politics. Parties whose origins are as victorious insurgent groups have different legacies and hence different institutional structures and patterns of behaviour than those that originated in breakaway factions of ruling parties, labour unions, non-violent social movements, or identity groups. Unlike classic definitions of political parties, post-rebel parties are not created around the need to win elections but rather as military organizations focused on winning an armed struggle. Key attributes of victorious rebel movements, such as cohesive leadership, discipline, hierarchy, and patterns of military administration of liberated territory, shape post-insurgent political parties and help explain why post-insurgent parties are often strong and authoritarian. This article seeks to identify the mechanisms that link rebel victory in three East African countries (Uganda, Ethiopia, and Rwanda) to post-war authoritarian rule. These processes suggest that how a civil war ends changes the potential for post-war democratization.